Dominion: England and its island neighbours, 1500 - 1707 - Hirst, Derek (Oxford histories, 2012)
"Dominion: England and its Island Neighbours c.1500-1707 is a rich narrative history of England's increasing dominance over the cluster of territories that became known as the British Isles. It brings alive a period and a geography remarkable for repeated religious wars and a long colonial struggle as well as for London's emergence as a political, economic, and cultural hub. While Dominion concentrates on English actions and purposes, it pays careful attention to interactions in Ireland, Scotland, and Wales, and to the pressures of European competition. It does so by drawing on the vibrant recent scholarship of the separate nations and considerable primary research, and also on the language of the actors, from Henry VIII and Elizabeth, Spenser and Shakespeare, to Oliver Cromwell and John Milton. Its purpose is not just to explore English understandings and ideologies, but their consequences, both creative and disruptive. The landmarks of the Tudor and Stuart centuries may be familiar: the creation of Ireland as a subordinate but fractured kingdom, the unification of Wales with England, the unstable union of the crowns of England and Scotland, the bloody conquest and reconquest of Ireland, and the formation of the United Kingdom amid fierce rivalry with France. By interweaving these strands as a single coherent story of English reactions and projections, this book opens up a new understanding of this formative period in the history of these islands - and also of its fractious legacy."--Publisher's website